Step: 1
4x + 3y = 17 .....(1)
- x + 3y = 7 .....(2)
Step: 2
Equation 2 can be rearranged as x = 3y - 7 so that x in equation 1 can be replaced with this in order to solve the linear system.
Step: 3
4(3y - 7) + 3y = 17
[Replace x with 3y - 7 in Equation 1.]
Step: 4
15y - 28 = 17
[Combine like terms.]
Step: 5
15y = 45
[Add 28 to both sides.]
Step: 6
y = 3
[Divide each side by 15.]
Step: 7
x = 3y - 7 = 3(3) - 7
[Replace y with 3 in the revised Equation 2.]
Step: 8
Step: 9
The solution for the linear system is (2, 3).
Correct Answer is : (2, 3)